Novel pathophysiological markers are revealed by iTRAQ-based quantitative clinical proteomics approach in vascular dementia - Lai, Mitchell K. P. (2014)
Vascular dementia (VaD) is a leading cause of dementia in the elderly together with Alzheimer's disease with limited treatment options. Poor understanding of the pathophysiology underlying VaD is hindering the development of new therapies. Hence, to unravel its underlying molecular pathology, an iTRAQ-2D-LC–MS/MS strategy was used for quantitative analysis of pooled lysates from Brodmann area 21 of pathologically confirmed cases of VaD and matched non-neurological controls. A total of 144 differentially perturbed proteins out of 2284 confidently identified proteins (false discovery rate = 0.3%) were shortlisted for bioinformatics analysis. Western blot analysis of selected proteins using samples from individual patients (n = 10 per group) showed statistically significant increases in the abundance of SOD1 and NCAM and reduced ATP5A in VaD. This suggested a state of hypometabolism and vascular insufficiency along with an inflammatory condition during VaD. Elevation of SOD1 and increasing trend for iron-storage proteins (FTL, FTH1) may be indicative of an oxidative imbalance that is accompanied by an aberrant iron metabolism. The synaptic proteins did not exhibit a generalized decrease in abundance (e.g. syntaxin) in the VaD subjects. This reported proteome offers a reference data set for future basic or translational studies on VaD.